Burgers for tourists who give a damn! Driving disruptive social change upstream and downstream in the tourist food supply chain. Issue 11 (2nd November 2017) - Carrigan, Marylyn; Lazell, Jordon; Bosangit, Carmela; Magrizos, Solon
ABSTRACT: Using the theoretical lens of social capital, this paper examines the role of small tourist food businesses and their impact on the sustainability of the destination and local food supply chains. The paper analyses the experiences of small business owner-managers highlighting the complex and subtle nature of the socially responsible strategies used to progress sustainability in a tourist destination. The findings show that authentic lifestyles, motivated by intrinsic not just extrinsic rewards, are driving disruptive social change upstream and downstream in the tourist food supply chain. Small food business owner-managers are catalysts for "common" good, and as supporters for ethical and sustainable food chains have considerable local tourism influence and impact. Social capital strengthens their sense of destination ownership and fuels an obligation to protect their fragile tourist resources. The intersection between social capital, authenticity and responsibility among small food businesses in the tourist industry is demonstrated.